HOW RELIGIOSITY, KNOWLEDGE, AND CHARACTERISTICS OF MUZAKKI AFFECT ZAKAT COMPLIANCE - Ach Yasin; Rachma Indrarini; Sri Abidah Suryaningsih (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2022)
Several things affect the achievement of targets, such as internal and external factors of the zakat management organization. The level of compliance with paying zakat is one of the external factors that can affect the receipt of zakat. So, this research will examine indicators that affect the level of compliance to pay zakat in Indonesia, using religiosity, knowledge, and characteristics of muzakki. The approach in this research is a quantitative approach with probit regression. This research collects 200 respondents as samples from Muslim-majority areas, such as East Java, Yogyakarta, Central Java, and South Sulawesi. It is hoped that this research will find indicators that can influence the level of muzakki compliance in paying zakat. The probit regression results, of all the variables used, there are two significant variables, namely religiosity and knowledge. Meanwhile, demographic variables such as age, income, education, marital status, and gender are insignificant because some people who pay zakat are not based on whether they have reached nishab. They always set aside 2.5% of their income for zakat after payday. The statement reinforces other evidence that people who pay zakat in Indonesia are more driven by factors of faith and trust. Theoretically, this study offers a new research model to explain muzakki compliance in paying zakat. Empirically, this research contributes to zakat managers' focus programs on increasing religiosity and knowledge of muzakki.